Hormonal and metabolic influences on outcomes in PCOS undergoing assisted reproduction: the role of BMI in fresh embryo transfers - Li Wang; Xiaoyu Yu; Dongsheng Xiong; Mei Leng; Meiyu Liang; Rong Li; Libing He; Heqiu Yan; Xiaoju Zhou; Erniu Jike; Weixin Liu; Jiuzhi Zeng (BMC Pregnancy and Childbirth)
Abstract Background This retrospective study aimed to examine the influence of hormonal and metabolic parameters across varying body mass index (BMI) levels on embryo quality and pregnancy outcomes in fresh embryo transfer cycles using assisted reproductive technology (ART) in patients diagnosed with polycystic ovary syndrome (PCOS). Methods A total of 167 women diagnosed with PCOS and 266 women without PCOS (control group) were included. Metabolic and hormonal parameters was compared between the two groups to evaluate their relationship with embryo quality and pregnancy outcomes. Subgroup analyses were performed to assess these effects in patients with normal and high BMI. Results In the PCOS group, hormonal and metabolic parameters such as insulin, blood lipids, luteinizing hormone (LH), anti-Müllerian hormone (AMH) and antral follicle counting (AFC) were significantly higher than in the control group. The PCOS group also produced more blastocysts and a higher proportion of high-quality blastocysts. However, pregnancy rate and clinical pregnancy rates were similar between the two groups, regardless of BMI. Among the high-BMI PCOS patients, the miscarriage rate was significantly higher compared to the control group, and its rate showed a positive correlation with BMI, LH, and total testosterone (TSTO) levels. Conclusion Hormonal imbalances and glucose-lipid metabolism have minimal influence on embryo development in PCOS patients. However, hormonal factors-particularly in PCOS patients with high BMI—significantly influence pregnancy outcomes, with elevated BMI and androgen levels increasing the risk of miscarriage. These findings underscore the importance of addressing metabolic and hormonal factors in the management of PCOS patients undergoing ART.